Escribir la mirada. Inteligencia de la DIPBA y la DGI sobre estudiantes universitarios - Dagatti, Mariano Jesús (2018)
The article explores the organization, control and espionage activities of the intelligence archives in Argentina, and their communication protocols. The aim is to present preliminary results of a comparative study of intelligence reports about students made by informants from the DIPBA (1959-1974) and the DGI (1967-1975). It investigates the spies’ writing style and the ways students under constant surveillance are described. The article is organized into three sections: the first outlines the predominant discursive genres in the corpus, taking into account the communication routines of the communities studied; the second includes a description of the textual sequences that organize the transcription of the gaze; the third analyzes the description of the students and professors under surveillance and the construction of an anti-ethical world. The article concludes that a “hidden” service paradoxically found it difficult to control the public dissemination of its adversaries' worldview.